Antimicrobial dispensing practices and determinants of antimicrobial resistance: a qualitative study among community pharmacists in Pakistan. Issue 3 (12th July 2019) - Saleem, Zikria; Hassali, Mohamed Azmi; Hashmi, Furqan Khurshid; Godman, Brian; Saleem, Fahad
Abstract : Background: There are concerns with the extent of dispensing of antibiotics among community pharmacists in Pakistan often without a prescription adding to antimicrobial resistance (AMR) rates. Objective: To explore the determinants of AMR and the pattern of antimicrobial dispensing among community pharmacists. Design: In this qualitative study design, a semistructured interview guide was developed based on an in-depth review of published papers. Audio-recorded interviews with transcripts were analysed by thematic content analysis. Setting: Interviews were conducted among community pharmacists in Lahore, Pakistan. Participants: In order to obtain individual points of view, in-depth face-to-face interviews with purposively selected pharmacists were conducted. Results: A total of 12 pharmacists were interviewed for the study. After analysis, four major themes emerged: (1) knowledge and perception of community pharmacists about antimicrobials, (2) antimicrobial dispensing practices of community pharmacists, (3) determinants of AMR, (4) potential interventions to control AMR. Most of the pharmacists have limited knowledge about AMR, antimicrobial stewardship programmes and related guidelines. However, all the pharmacists strongly agreed that different appropriate actions should be taken in order to rationalise future antimicrobial use. Conclusion: The results indicated that irrational antimicrobial dispensing and use is common among community pharmacists in Pakistan owing to lack of knowledge. The community pharmacists perceived that behaviour of patients and the societal environment contributed to irrational antimicrobial use and subsequent development of AMR. They suggested a need for a multidisciplinary framework in order to improve future antimicrobial use and reduce AMR in Pakistan.